Kyrgyz Republic : Request for Purchase Under the Rapid Financing Instrument and Disbursement under the Rapid Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2020)
The outbreak of the COVID-19 pandemic has weakened the macroeconomic outlook. The authorities have launched a health care contingency plan and an initial package of economic measures, together totaling USD 31 million (0.4 percent of GDP), and are preparing a second, larger package of economic measures of about USD 400 million (5.2 percent of GDP). To help address an urgent balance of payments need arising from the pandemic, estimated at about USD 500 million, the authorities request an additional purchase under the Rapid Financing Instrument (RFI) of 33.3 percent of quota (SDR 59.2 million) and a disbursement under the Rapid Credit Facility (RCF) of 16.7 percent of quota (SDR 29.6 million) under the 'exogenous shock' window of the RCF. This follows Board approval on March 26, 2020 of the authorities' earlier request for the same amounts, before the doubling of the annual access on emergency financing under the 'exogenous shock' window of the Rapid Credit Facility (RCF) to 100 percent of quota was approved on April 6, 2020. This additional request will bring the total purchases under the RFI and the disbursements under the RCF to 100 percent of quota in 2020.